2020
DOI: 10.2147/cmar.s229013
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA EMX2OS Induces Proliferation, Invasion and Sphere Formation of Ovarian Cancer Cells via Regulating the miR-654-3p/AKT3/PD-L1 Axis</p>

Abstract: Long noncoding RNA (lncRNA) deregulation is frequent in human ovarian cancers (OCs), but the role of specific miRNAs involved in this disease remains elusive. LncRNA EMX2OS was previously reported to act as an oncogene in human cancers. However, their accurate expression, function and underlying mechanisms in OC are largely unclear. Materials and Methods: The levels of EMX2OS in OC tissues and cell lines were determined by quantitative real-time PCR, and the function of EMX2OS was then analyzed both in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 31 publications
0
49
1
Order By: Relevance
“…It was shown, however, to be highly expressed in hepatocellular carcinoma and inhibited the transcription of THBS1 by recruiting DNMT3b to its promoter region [ 34 ]. Previous research has revealed that the downregulation of EMX2OS in classical papillary thyroid cancer might independently predict shorter recurrence-free survival [ 35 ], while the overexpression of EMX2OS in ovarian cancer and EMX2OS/miR-654/AKT3 axis may target PD-L1 (programmed cell death protein 1) to suppress the initiation and progression of cancer [ 36 ]. Accumulating evidences have suggested that Thrombospondin-1 (THBS1) may affect tumor immunity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown, however, to be highly expressed in hepatocellular carcinoma and inhibited the transcription of THBS1 by recruiting DNMT3b to its promoter region [ 34 ]. Previous research has revealed that the downregulation of EMX2OS in classical papillary thyroid cancer might independently predict shorter recurrence-free survival [ 35 ], while the overexpression of EMX2OS in ovarian cancer and EMX2OS/miR-654/AKT3 axis may target PD-L1 (programmed cell death protein 1) to suppress the initiation and progression of cancer [ 36 ]. Accumulating evidences have suggested that Thrombospondin-1 (THBS1) may affect tumor immunity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al showed that miR-654-3p is reduced in liver cancer and hinders tumor cell growth and invasion in vitro [ 28 ]. Duan et al demonstrated that lncRNA EMX2OS encouraged the progression of ovarian cancer cells by targeting the miR-654-3p/AKT3/PD-L1 pathway [ 29 ]. Jin et al demonstrated that circRNA circHIPK3 is a prognostic biomarker in glioma development by modulating the miR-654/IGF2BP3 axis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs affect the malignant cell proliferation, migration and invasion capacities at post-transcriptional regulation level via binding to the 3 -UTR of the target mRNA (Yu et al, 2018;Ali Syeda et al, 2020). Reportedly, miR-654-3p targets several genes associated with malignancy, such as P21 in gastric cancer (Deng et al, 2020), AKT3 in ovarian cancer (Duan et al, 2020), and 6 | Reversal effect on proliferation and migration by upregulating miR-654-3p and SRC simultaneously. Relative expression levels of miR-654-3p and SRC in HCT116 and SW480 transfected with miR-NC + NC plasmid, miR-654-3p + NC plasmid or miR-654-3p + SRC plasmid at mRNA level (A) and protein level (B).…”
Section: Discussionmentioning
confidence: 99%